Autophagy and lysosomal dysfunction: A new insight into mechanism of synergistic pulmonary toxicity of carbon black-metal ions co-exposure. (January 2017) - Kong, Huating; Xia, Kai; Pan, Liang; Zhang, Jichao; Luo, Yan; Zhang, Yu; Cui, Zhifen; El-Sayed, Nahed Nasser; Aldalbahi, Ali; Chen, Nan; Li, Aiguo; Tai, Renzhong; et al.
Abstract: Fine particulate matter (PM 2.5) is the principal instigators of adverse health events, yet gaps still remain in understanding the mechanism mediating its toxic response. Similar to nanoparticles, PM 2.5, with large surface area to volume ratio, can absorb multipollutants in air, displaying toxicity profiles that are very different from those of coarse particles of the same composition. One particularly relevant interaction is that of PM 2.5 and the anthropogenic metals. In this study, we used carbon black nanoparticle (CBs) and metal ions as model materials to investigate the synergistic pulmonary toxicity and its mechanism. We demonstrated that excessive metal contaminants adsorbed on CBs contributed to the observed toxic effects both in vitro and in C57BL6 mice intratracheal instillation model. Significantly, we found that autophagy and lysosomal dysfunction accounted for the synergistic pulmonary toxic effect of co-exposure to CBs and metals. Our findings provide a new insight into understanding the toxicological and healthy effects of fine particles, which have potential to aid in mitigating their adverse health effect.